2000
DOI: 10.1093/humupd/6.4.332
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and biochemical mechanisms by which environmental oestrogens influence reproductive function

Abstract: The biology and physiology of the male as well as female reproductive system is hormonally regulated. Abnormalities in the dynamics of hormone production, metabolism and elimination, as well as their binding to certain target tissues, has been associated with pathophysiological conditions of the reproductive system. Although oestrogens are known to be one of the major hormone groups in regulating the reproductive function and the fertilization process, the cellular and biochemical mechanism or mechanism(s) via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 175 publications
(231 reference statements)
1
69
0
4
Order By: Relevance
“…In particular, the increases in the concentrations of active phytoestrogen metabolites in the blood plasma of the early-pregnant heifers may enable these substances to influence the secretory functions of the reproductive system. Our previous studies and those of other authors have shown studies that not only high, but also low concentrations of phytoestrogens are widespread, have substantial deleterious effects on the reproductive processes and may cause severe disorders during the estrous cycle and development of early pregnancy in many animal species [5,6,[23][24][25][26]. In particular, the problem of estrogen-dependent infertility has been studied extensively in ewes [5].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the increases in the concentrations of active phytoestrogen metabolites in the blood plasma of the early-pregnant heifers may enable these substances to influence the secretory functions of the reproductive system. Our previous studies and those of other authors have shown studies that not only high, but also low concentrations of phytoestrogens are widespread, have substantial deleterious effects on the reproductive processes and may cause severe disorders during the estrous cycle and development of early pregnancy in many animal species [5,6,[23][24][25][26]. In particular, the problem of estrogen-dependent infertility has been studied extensively in ewes [5].…”
Section: Discussionmentioning
confidence: 99%
“…As agonists and/or antagonists of endogenous estrogens, phytoestrogens may induce various pathologies in the female reproductive tract including disorders in the function of the ovary, oviduct, and uterus [14]. We recently showed that phytoestrogens present in soy beans (genistein and daidzein) and their active metabolites (equol and para-ethyl-phenol; respectively) decrease fertility in cows [15].…”
mentioning
confidence: 99%
“…A presença dos xenormônios no ambiente tem causado preocupações sobre o impacto destas substâncias na saúde humana (103). A exposição se dá principalmente pela alimentação e as suas conseqüências estão longe de serem conhecidas, quer durante a vida intra-uterina, quer no desenvolvimento e suas repercussões na reprodução.…”
Section: Efeitos Adversosunclassified